Odpowiedzi

Najlepsza Odpowiedź!
2010-02-03T21:26:42+01:00
7)A=3x^-xy, B= -2y , c=3x
a)
(A*B)*C=[3x^-xy *(-2y)]*3x=(-6x^y +2xy^)*3x=-18xdo trzeciejy+6x^y^
b)
A*(B*C)=3x^-xy*[(-2y)*3x]=3x^-xy * (-6xy)= -18xdo trzeciejy+6x^y^
c)
(A+B)*C=[3x^-xy +(-2y)]*3x=(3x^-xy-2y)*3x=9x do trzeciej-3x^y-3xy^
d)
A*C+B*C=3x^-xy*(-2y) +(-2y)*3x= -6x^y+2xy^-6xy

zad.2)
a)
3(x^-2x+3)-2(x^-5x-1)=3x^-6x+9-2x^+10x+2=
x^+4x+11=2^+4*2+11=4+8+11=23
b)
a(2ab+b)-b(a-2ab+a^)=2a^b+ab-ab+2ab^+a^=a^ +2a^b+2ab^=
(0,1)^+2*(0,1)^*(-10)+2*0,1 * (-10)^=0,01-0,2-2=- 2,19

( ^-------------->oznacza do kwadratu)